Мы живем среди людей: Кодекс поведения / Сост. И. В. Дубровина - Дубровина И. В. (Политиздат, 1989)
Экземпляры: (20160225) / Инвентарный номер: 24544 / Цена: / Сис.шифр: 87.7 / Авт.знак: М 94 / ББК: 87.774